2021
DOI: 10.1002/jhbp.903
|View full text |Cite
|
Sign up to set email alerts
|

Precision vascular anatomy for minimally invasive distal pancreatectomy: A systematic review

Abstract: Background Minimally invasive distal pancreatectomy (MIDP) is increasingly performed worldwide; however, the surgical anatomy required to safely perform MIDP has not yet been fully considered. This review evaluated the literature concerning peripancreatic vascular anatomy, which is considered important to conduct safe MIDP. Methods A database search of PubMed and Ichushi (Japanese) was conducted. Qualified studies investigating the anatomical variations of peripancreatic vessels related to MIDP were evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 109 publications
(246 reference statements)
0
21
0
2
Order By: Relevance
“…However, no other large‐scale studies have compared these two approaches 19 . Variations in the anatomical location of the SpA root may affect the difficulty and the surgical outcomes of the approach to the SpA during MIDP 18‐20 . The survey revealed that 36% of experts considered the anterior approach to be the first choice, while 8% considered the posterior approach to be the first choice.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, no other large‐scale studies have compared these two approaches 19 . Variations in the anatomical location of the SpA root may affect the difficulty and the surgical outcomes of the approach to the SpA during MIDP 18‐20 . The survey revealed that 36% of experts considered the anterior approach to be the first choice, while 8% considered the posterior approach to be the first choice.…”
Section: Resultsmentioning
confidence: 99%
“…As the first step in this project, we reviewed the available evidence in the literature. As expected, very few studies provided scientific evidence that could ensure the recommendations 18,19 . Most of the articles reviewed were case series and case reports that were categorized as “expert opinions,” and few RCTs and comparative studies with large numbers of patients were identified.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Using computed tomography performed before surgery and intraoperative ndings from operation records, we investigated the anatomy of the LGV and classi ed it into four types according to the running pattern of the LGV, ventral or distal route of the common hepatic artery (CHA) and splenic artery (SpA) arcade, and joining point to the veins of the portal vein (PV) or splenic vein (SpV). Previous reports have identi ed three positions for LGV con uence into major veins: the PV, SpV, and junction of the PV and SpV [15,16]. However, Kawasaki et al described a relationship between the LGV and arteries around the pancreas [17].…”
Section: Running Pattern Of Lgv Classi Cationmentioning
confidence: 99%